Efectos sobre la Argentina de la ampliación de la Unión Europea - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2004)
– In May 2004 ten new members are incorporated to the European Union (EU) which, considered on the whole, represent a GDP which is four times greater than the Argentine GDP. With this expansion, the EU population will increase by 24%, its surface will increase by 28%, and the GDP will increase by only 5%. From the trade viewpoint, the expansion of the EU means a potential opportunity for the Argentine Republic as well as a tangible threat: having tariff preferences in a wider market once the Mercosur - European Union free trade agreement is entered into, and the possibility that the Argentine Republic is replaced as a supplier of the current EU (15 countries) by the new partners. In this analysis, it must be taken into account that the potential impact on trade will not be abrupt, since the expansion process of the EU took place gradually, and the new partners have had tariff preferences in the EU-15 for a long time. In fact, the European Agreements, signed at the beginning of the nineties, provided an institutional framework for the bilateral relationships between the countries of Central and Western Europe, and the EU which resulted in the free trade of industrial products, while, for the agricultural products, instead, the parties agreed upon a gradual liberalization.
Keywords: 330; EU-Erweiterung; Internationale Wirtschaftsbeziehungen; Argentinien; EU-Staaten